2020
DOI: 10.3892/mmr.2020.11356
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of methylated septin 9 are capable of detecting hepatocellular carcinoma and hepatic cirrhosis

Abstract: Hepatocellular carcinoma (Hcc) was the third most common cause of cancer-associated mortality in china in 2015. early detection of Hcc and hepatic cirrhosis (Hc) can serve a crucial role in the prevention and therapeutic intervention of these diseases. current early detection methods rely on less sensitive imaging modalities compared with the pathological examination. in the present study, a total of 64 patients with Hcc, 44 patients with Hc and 298 individuals with no evidence of disease (ned) were recruited,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…1 ). Eventually, the full text of 59 eligible articles (60 studies) was incorporated into this meta-analysis ( Huang et al, 2003 ; Wang et al, 2021 ; Wong et al, 2000 ; Wong et al, 2003 ; Chu et al, 2004 ; Lin et al, 2005 ; Yeo et al, 2005 ; Iizuka et al, 2006 ; Ren et al, 2006 ; Wang et al, 2006 ; Zhang et al, 2007 ; Chan et al, 2008 ; Chang et al, 2008 ; Igetei et al, 2008 ; Ahmed et al, 2010 ; El-Shazly et al, 2010 ; Hu et al, 2010 ; Huang et al, 2011 ; Iizuka et al, 2011 ; Yang et al, 2011 ; Chen et al, 2012 ; Huang et al, 2012 ; Mohamed et al, 2012 ; Chen et al, 2013 ; Sun et al, 2013 ; Zhang et al, 2013 ; Han et al, 2014 ; Huang et al, 2014 ; Ji et al, 2014 ; Kuo et al, 2014 ; Li et al, 2014 ; Yang et al, 2014 ; Dong et al, 2015 ; Huang et al, 2015 ; Ramadan et al, 2015 ; Teng et al, 2016 ; Dong et al, 2017 ; Hu et al, 2017 ; Mansour et al, 2017 ; Tian et al, 2017 ; Wu et al, 2017 ; Gai et al, 2018 ; Li et al, 2018 ; Oussalah et al, 2018 ; Wei et al, 2018 ; Linlin et al, 2018 ; Bai et al, 2019 ; Kisiel et al, 2019 ; Marchio et al, 2019 ; Pasha, Mohamed & Radwan, 2019 ; El-Bendary et al, 2020 ; He et al, 2020 ; Kotoh et al, 2020 ; Li et al, 2020a …”
Section: Resultsunclassified
See 2 more Smart Citations
“…1 ). Eventually, the full text of 59 eligible articles (60 studies) was incorporated into this meta-analysis ( Huang et al, 2003 ; Wang et al, 2021 ; Wong et al, 2000 ; Wong et al, 2003 ; Chu et al, 2004 ; Lin et al, 2005 ; Yeo et al, 2005 ; Iizuka et al, 2006 ; Ren et al, 2006 ; Wang et al, 2006 ; Zhang et al, 2007 ; Chan et al, 2008 ; Chang et al, 2008 ; Igetei et al, 2008 ; Ahmed et al, 2010 ; El-Shazly et al, 2010 ; Hu et al, 2010 ; Huang et al, 2011 ; Iizuka et al, 2011 ; Yang et al, 2011 ; Chen et al, 2012 ; Huang et al, 2012 ; Mohamed et al, 2012 ; Chen et al, 2013 ; Sun et al, 2013 ; Zhang et al, 2013 ; Han et al, 2014 ; Huang et al, 2014 ; Ji et al, 2014 ; Kuo et al, 2014 ; Li et al, 2014 ; Yang et al, 2014 ; Dong et al, 2015 ; Huang et al, 2015 ; Ramadan et al, 2015 ; Teng et al, 2016 ; Dong et al, 2017 ; Hu et al, 2017 ; Mansour et al, 2017 ; Tian et al, 2017 ; Wu et al, 2017 ; Gai et al, 2018 ; Li et al, 2018 ; Oussalah et al, 2018 ; Wei et al, 2018 ; Linlin et al, 2018 ; Bai et al, 2019 ; Kisiel et al, 2019 ; Marchio et al, 2019 ; Pasha, Mohamed & Radwan, 2019 ; El-Bendary et al, 2020 ; He et al, 2020 ; Kotoh et al, 2020 ; Li et al, 2020a …”
Section: Resultsunclassified
“…Table S1 summarizes the characteristics of all 59 papers ( n = 92). All the included studies included quantitative analysis to measure ctDNA concentration and single-gene methylation concentration ( n = 19) ( Wang et al, 2021 ; Iizuka et al, 2006 ; Ren et al, 2006 ; Chan et al, 2008 ; El-Shazly et al, 2010 ; Iizuka et al, 2011 ; Yang et al, 2011 ; Chen et al, 2012 ; Huang et al, 2012 ; Mohamed et al, 2012 ; Chen et al, 2013 ; He et al, 2020 ; Kotoh et al, 2020 ; Li et al, 2020a ; Xie et al, 2021 ; Mansour et al, 2017 ; Gai et al, 2018 ; Linlin et al, 2018 ; El-Bendary et al, 2020 ) and qualitative analysis of tumor-specific ctDNA single gene-mutation and methylation ( n = 40) ( Wong et al, 2000 ; Wong et al, 2003 ; Chu et al, 2004 ; Lin et al, 2005 ; Yeo et al, 2005 ; Wang et al, 2006 ; Zhang et al, 2007 ; Chang et al, 2008 ; Igetei et al, 2008 ; Ahmed et al, 2010 ; Hu et al, 2010 ; Huang et al, 2011 ; Sun et al, 2013 ; Zhang et al, 2013 ; Han et al, 2014 ; Huang et al, 2014 ; Ji et al, 2014 ; Kuo et al, 2014 ; Li et al, 2014 ; Yang et al, 2014 ; Dong et al, 2015 ; Huang et al, 2015 ; Ramadan et al, 2015 ; Teng et al, 2016 ; Dong et al, 2017 ; Hu et al, 2017 ; Tian et al, 2017 ; Wu et al, 2017 ; Li et al, 2018 ; Oussalah et al, 2018 ; Wei et al, 2018 ;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other single methylated ctDNA biomarkers tested in case–control studies include genes encoding for Ras association domain family 1A ( RASSF1A ) [ 86 , 87 ], vimentin ( VIM ) [ 88 ], fibulin 1 ( FBLN1 ) [ 88 ], and tissue factor pathway inhibitor-2 (TFPI2) [ 98 ]. More recently, methylated septin 9 ( SEPT9 ) gene, the biomarker used in the first blood-based test commercialized for the early detection of colorectal carcinoma, has demonstrated high accuracy (area under the receiver operating curve, AURC, of 0.94) to diagnose HCC in two independent cohorts [ 94 ] and to predict long-term survival of HCC patients [ 95 ]. SEPT9 is a key regulator of cell division implicated in liver carcinogenesis [ 110 ], which is silenced by promoter hypermethylation not only in HCC [ 58 ] and colorectal cancer, but also in other tumors such as head and neck squamous cell carcinoma and breast cancer [ 111 , 112 ].…”
Section: Epigenetic Biomarkers In Liquid Biopsy: Methylated Ctdna mentioning
confidence: 99%
“…Moreover, the combination of these emerging epigenetic biomarkers with currently used serological markers can be envisioned to be used to improve HCC diagnosis, patient stratification, and evaluation of treatment response. In this regard, several studies have shown increased sensitivity when their identified epigenetic liquid biopsy biomarkers are combined with AFP determination [ 93 , 95 , 98 ]. The presence and levels of naïve viral RNA and DNA [ 119 ], its integration in cellular DNA, or even epigenetic modifications of viral sequences [ 84 ] along the hepatocarcinogenesis process could also be combined.…”
Section: Epigenetic Biomarkers In Liquid Biopsy: Methylated Ctdna mentioning
confidence: 99%